Oligogenic effect is associated with the clinical heterogeneity of autosomal dominant deafness-15 - Jianyan Pan; Hua Teng; Fang Liu; Siyi Chen; Yaning Liu; Yanling Teng; Desheng Liang; Zhuo Li; Lingqian Wu (Scientific Reports)
Abstract Autosomal dominant deafness-15 which is caused by mutation in the POU4F3 gene, has been reported with a wide degree of clinical heterogeneity, even between intrafamilial members. However, the reason is still elusive. In this study, A four-generation Chinese family with 11 patients manifesting late-onset progressive non-syndromic hearing loss was recruited. The phenotype of hearing loss in this family showed a large variability in terms of onset age and progression speed. A novel mutation (c.706 C > T, p.L236F) was identified by the whole exome sequencing, and its pathogenicity was confirmed by altering the subcellular localization of POU4F3. In addition, we found that two individuals with earlier age of onset and more rapid progression of hearing loss carry additional pathogenic variants in other deafness genes (III-7, STRC:c.4057 C > T; IV-1, GJB2:c.109G > A; CDC14A:c.935G > A). By using the real time quantitative PCR, western blot, luciferase assays and electrophoretic mobility-shift assay, POU4F3 was proved to directly regulate the expression of STRC, GJB2 and CDC14A respectively. ChIP-seq further revealed that POU4F3 can also bind to a series of deafness genes. In summary we expanded the mutation spectrum of POU4F3 by identifying a novel mutation and its pathogenicity. Meanwhile, three genes STRC, GJB2 and CDC14A were validated as POU4F3 new targets, implicating that the variants in the three genes may play a role of genetic modifier to generate a synergistic and enhancement effect on the progression of DFNA15.